Investigação da eficácia e segurança da lidocaína gel para realização de injeção intravitrea - Shiroma, Helio Francisco [UNIFESP] (2017)
Purpose: Five studies were performed in order to: 1. Investigate the safety to the cornea and anesthetic efficacy of five concentrations of lidocaine gel during intravitreal injection procedure. 2. Cognize the anesthetic preference for intravitreal injection among Brazilian retina and vitreous specialists. 3. Evaluate the efficacy and anesthetic duration between lidocaine gel at concentrations of 2% and 5%. 4. Compare pain in patients undergoing IVI with topical anesthesia with or without 2% lidocaine gel. 5. Perform a systematic review to evaluate the effectiveness of different local anesthetic techniques for IVI. Methods: 1. A prospective clinical trial was conducted to evaluate patient pain of intravitreal injection, testing lidocaine gel in five preparations: 2%, 3.5%, 5%, 8% and 12%. 2. Electronic research with 22 questions about preferences to perform intravitreal injection, among the members of the Brazilian Retinal and Vitreous Society. 3. Comparison of pain at conjunctival clamping at the fifth and tenth minutes in 80 eyes anesthetized with 2% and 5% lidocaine gel. 4. Comparison of intravitreal injection pain in 40 patients under topical proparacaine with or without lidocaine gel. 5. Studies to be considered for inclusion were identified by searching the following electronic bibliographic databases: Cochrane, LILACS, PubMed, Scopus and Web of Science. The search date ended February 19, 2016. Results: 1. Mean pain score among all groups was similar (p= 0.077). There was no significant difference between groups in regard to keratitis mean score (p= 0.897). 2. About 65% of the procedures are performed under topical anesthesia with anesthetic eye drops, 22% under eye drops + anesthetic gel, 5% with subconjunctival infiltration of lidocaine and 7% with other associations and sedation. 3. At the tenth minute, 5% lidocaine anesthesia was statistically more effective at conjunctival clamping. 4. The discomfort during placement of the blepharostat and intravitreal injection pain was lower in the group of the anesthetic eye drops with the lidocaine gel 2%. 5. The discomfort of intravitreal injection is mild, and there is no anesthetic technique that can be considered as standard. Conclusion: 1. Lidocaine gel at concentrations from 2% to 12% induced similar anesthetic effect for IVIs without adverse effects on cornea and conjunctiva. 2. Topical anesthesia with eye drops is the preferred technique for intravitreal injection among Brazilian retinal and vitreous specialists. 3. Five percent and 2% lidocaine gels have similar efficacy controlling pain five minutes after instillation, but 5% lidocaine gel appears to be more effective with a longer duration of action, without corneal toxicity. 4. The association of the topical anesthetic with gel is positive in pain relieve of intravitreal injection. 5. Different anesthetic options are similar in relation to pain at the time of injection.